Profile of Injection Drug Users in Kermanshah, Iran - Hamid Gheibipour; Soheila Khodakarim; Asaad Sharhani; Koorosh Etemad; Abolghasem Shokri (Shahrekord University of Medical Sciences, 2020)
Background and aims: Injection drug use is considered as an international public health threat that can lead to serious health-related outcomes. The aim of this study was to obtain a profile of injection drug users (IDUs) in Kermanshah, Iran, in 2017. Methods: This cross-sectional study was carried out on 606 male IDUs who were recruited from 2 drop-in centers in Kermanshah using a snowball sampling method. Continuous and categorical variables are expressed as the mean and standard deviation, as well as frequency and percentage, respectively. Results: The mean age of participants in this study was 36.7±8.51 years and at first drug injection was 29.35±8.04 years. In addition, the highest frequency of injection drugs belonged to heroin (99.00%), methamphetamine (86.00%), and opium (85.00%), respectively. However, the lowest injection drugs were opium syrup (0.50%), ecstasy (0.50%), and amphorphine (0.20%). Conclusion: Based on the findings of this study, heroin, methamphetamine, and opium had the highest frequency injection among male IDUs in Kermanshah, and the age of the first drug injection was low among these individuals. Accordingly, wider coverage prevention programs are highly recommended, including harm reduction programs, counseling centers with improved quality of services, treatment programs, and greater attention to human resource development-based counseling and education.